Предмет: Алгебра, автор: Аноним

Упростить выражение, помогите пожалуйста с Алгеброй!

Приложения:

Ответы

Автор ответа: paradiseva
0
(1+2 sqrt[4]{x} + frac{x- sqrt{x} }{ sqrt{x} -1} ) cdot frac{x^{ frac{1}{4} }-1}{x^{ frac{1}{4} }+1} =(1+2 sqrt[4]{x} + frac{ sqrt{x} ( sqrt{x} - 1) }{ sqrt{x} -1} ) cdot frac{x^{ frac{1}{4} }-1}{x^{ frac{1}{4} }+1} =\
=(1+2 sqrt[4]{x} +  sqrt{x} ) cdot  frac{ sqrt[4]{x} -1}{ sqrt[4]{x} +1} =
(1^2+2cdot1cdot sqrt[4]{x} +( sqrt[4]{x} )^2 ) cdot  frac{ sqrt[4]{x} -1}{ sqrt[4]{x} +1}=\
=(1 + sqrt[4]{x} )^2 cdot  frac{ sqrt[4]{x} -1}{ sqrt[4]{x} +1} =(1+ sqrt[4]{x} )(sqrt[4]{x} -1)=( sqrt[4]{x} )^2-1^2= sqrt{x} -1
Похожие вопросы